STUDY ON ADSORPTION OF RARE EARTH ELEMENTS BY KAOLINITE - Wan Y.; Liu C. (My University, 2005)
For better understanding the adsorption of rare earth elements (REEs) by clay minerals and its controlling factors, the experiments on adsorption of REEs in solutions with 1 g·L-1 kaolinite were performed at different conditions. The results are as follows: the REEs reach equilibrium in the adsorption-desorption process for 24; Langmuir's adsorption curve is used for modeling the adsorption of REEs by kaolinite; a general trend is that the higher the contents of REEs are, the less obvious the fractionation is. Furthermore, there is significant effect of pH on the adsorption and fractionation of REEs by kaolinite, and the REEs distribution coefficient increases with increasing pH. When pH is nearly neutral, as reaches 7, heavy REEs are more adsorbed than light REEs.
Keywords: ADSORPTION; DISTRIBUTION COEFFICIENT; KAOLINITE; PEDOLOGY; RARE EARTHS